(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective: In this study 50 patients of neck swelling were studied to compare the findings with clinical diagnosis and histopathological report for its diagnostic reliability. Methods: This cross sectional study was done in ENT Department of Sher-E-Bangla Medical College Hospital, Barisal, Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital, Dhaka from July 2006 to December 2006. Fine needle aspiration cytology, MRI, CT scan, and histopathological examination of postoperative specimen of neck swelling, analyzed data presented by various tables, graphs and figures. Results: In the present series 50 cases of neck swelling were studied. Out of these 50 cases 19 were male and 31 were female. The male, female ratio was 1:1.63. Age range was 4 60 years with maximum frequency in the 4th decade with the 3rd and 2nd in the following suit. Most of the patient was poor. Clinical, cytological and histopathological diagnosis was available in all the cases. The three sorts of diagnoses were compared with each other. Histopathologically 12 cases were tubercular lymphadenopathy, 12 cases were nodular goiter, 5 cases were Metastatic carcinoma, 5 were thyroid carcinoma and another 5 cases were lymphoma, Rest were benign, congenital and nonspecific inflammatory conditions. Correct diagnosis was made by FNAC in 45 cases. In the rest 5 cases smear were unsatisfactory in 2 cases and gives inconclusive result, remaining 3 were follicular neoplasmand no definitive result were made which were subsequently diagnosed by histopathological examination as a follicular adenoma in 1 and follicular carcinoma in 2. Sensitivity of FNAC in the diagnosis of neck masses were found 91% for tuberculosis, 100% for metastatic carcinoma and also for salivary gland tumour. In case of nodular goiter sensitivity was 92%. But it is only 60% sensitive in case of thyroid malignancy, as FNAC can not demarcate clearly between follicular adenoma and follicular cell carcinoma. But its accuracy in diagnosing papillary carcinoma of thyroid was 100%. Conclusion: FNAC can reduce substantially the need of open biopsy for histopathological examination. Accuracy of FNAC will be improved with relevant information provided by clinicians. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10410 Bangladesh J Otorhinolaryngol 2012; 18(1): 23-29